Obsidian geochemistry, geoarchaeology, and lithic technology in northwestern Patagonia (Argentina). (June 2017) - Fernández, M. Victoria; Barberena, Ramiro; Rughini, Agustina A.; Giesso, Martín; Cortegoso, Valeria; Durán, Víctor; Romero Villanueva, Guadalupe; Borrazzo, Karen; Lucero, Gustavo; Garvey, Raven; MacDonald, Brandi Lee; Glascock, Michael D.
Abstract: We studied the organization of mobility of hunter-gatherers groups of northwestern Patagonia (Argentina) from an interdisciplinary perspective. We combined geochemical and technological characterization of obsidian assemblages from surface and stratigraphic contexts spanning the Holocene, and a preliminary geoarchaeological study of the sources. The goals were to assess the provenance, mode of supply, use, and discard of obsidian artifacts on the basis of information on the structure of the two main regional sources: Cerro Huenul, located in the lowlands, and Laguna del Maule, located in the Andean highlands. We conducted geoarchaeological field sampling at different altitudes of the Barrancas River fluvial deposits to study the geomorphic impact on the secondary structure of the highland source. Preliminary geoarchaeological results allow extending the area of availability up to 90 km towards the lowlands from the outcrops. In addition, we performed non-destructive XRF analyses on 266 lithic artifacts, which were placed along a continuum of reduction. 89% of the artifacts corresponded to the local Cerro Huenul source, while 11% to Laguna del Maule. While the artifacts made on Cerro Huenul obsidian were represented by the full reduction sequence, those from Laguna del Maule are only represented by advanced stages. We integrate these results with information on the frequencies of projectile points, ceramics, and rock-art motifs for the two main archaeological sites in the region: Cueva Huenul 1 and Cueva Yagui. These proxies indicate that the sites have different place use histories, providing a scheme for the analysis of human use of the regional landscape. Highlights: Geochemical and technological study of archaeological obsidian from Patagonia was conducted. Geoarchaeological study of obsidian sources extends the availability up to 90 km from the outcrop. 89% of the artifacts corresponded to the local Cerro Huenul source while 11% to Laguna del Maule. Only Cerro Huenul obsidian artifacts were represented by the full reduction sequence. The main regional sites have different place use histories according the results.